2022
DOI: 10.1159/000521948
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Low-Dose Paracetamol Administration for Ductal Closure and Microstructural Brain Development in Preterm Infants

Abstract: <b><i>Introduction:</i></b> Prophylactic low-dose paracetamol administration is used to induce closure of the ductus arteriosus. Effects on the neurological outcome in preterm infants remain unknown. We compared microstructural brain development in very preterm infants with and without exposure to prophylactic paracetamol by using MR-based diffusion tensor imaging. <b><i>Materials and Methods:</i></b> Infants aged &#x3c;32 gestational weeks born between Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Bearing this in mind, it is remarkable that we did not find any negative effect on neurodevelopmental outcome in infants who received prophylactic low‐dose paracetamol. Furthermore, the findings of the current study are supported by our previous work where we did not observe any impairment in microstructural and functional brain maturation after prophylactic low‐dose administration in the same cohort, but in some aspects even a maturational advance 21,22 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Bearing this in mind, it is remarkable that we did not find any negative effect on neurodevelopmental outcome in infants who received prophylactic low‐dose paracetamol. Furthermore, the findings of the current study are supported by our previous work where we did not observe any impairment in microstructural and functional brain maturation after prophylactic low‐dose administration in the same cohort, but in some aspects even a maturational advance 21,22 …”
Section: Discussionsupporting
confidence: 90%
“…In our previous studies, we found no impairment of functional and microstructural maturation processes in the brain of very preterm infants following prophylactic low‐dose paracetamol administration 21,22 . For the current study, we can report that we did not observe any negative effect of prophylactic low‐dose paracetamol administration neurodevelopmental outcome until a corrected age of 24 months in our cohort including 345 closely monitored very preterm infants.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Beyond that study, we further investigated the effect of prophylactic low-dose paracetamol administration on structural and functional brain development. We found no impairment on microstructural maturation processes in preterm infants following prophylactic low-dose paracetamol administration ( 12 ). The present study is the next step in the continuation of our investigations, in which we were the first to study functional brain development in very preterm infants with and without exposure to low-dose paracetamol exposure.…”
Section: Discussionmentioning
confidence: 80%
“…To shed some more light on the ongoing debate about the safety of prophylactic low-dose paracetamol administration and preterm brain development, we investigated its effect in a large cohort of very preterm infants. First we used magnetic resonance-based diffusion tensor imaging at term-equivalent age in preterm infants with and without exposure to prophylactic low-dose paracetamol and found no impairment of microstructural maturation processes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%